“My life during the lockdown”: reazioni ed emozioni in un campione di adolescenti europei durante la pandemia - Liberato, Daniela; Venturini, Paola; Nöthen-Garunja, Isabel (Il sogno della farfalla, 2021)
In this paper the authors discuss how the adolescents were among the most vulnerable individuals to experience the social confinement due to Covid-19 pandemic. Scientific literature launched an alert of psychopathological risk in this age group, recording an increase in the number of suicides and domestic violence. Netforpp European association proposed an online questionnaire called “My life during the lockdown” in some Italian schools and also in some European partner countries such as Croatia and Romania. The analysis of emotional reactions and relational changes experienced by the adolescents’ participants, has allowed to investigate and identify both protective and risk factors which characterized the exceptional pandemic circumstances. Further research is needed to evaluate the long-term effects. However, this study highlights how the ability to keep investing in relationships and to react to stressful events, by carrying out a creative activity, represents a pivotal point to preserve mental health.